ЩОДО ПИТАННЯ КЛАСИФІКАЦІЇ КОРПОРАТИВНИХ ВІДНОСИН - Volovyk, O.A. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2008)
There has been analyzed the content of corporative relations from the point of view of their classification into internal and external ones. There has been determined staff of corporative relations, it’s specification. Criteria have been identified in foreshortened discussion and the content of internal corporative relations has been disclosed. Doctrinal interpretation of corporative relations’ content in the aspect of Сorporative law development as well as determination of corporative arguments’ jurisdiction have been given.